Commissioning of a water calorimeter as a primary standard for absorbed dose to water in magnetic fields. (29th January 2019) - de Prez, Leon; de Pooter, Jacco; Jansen, Bartel; Woodings, Simon; Wolthaus, Jochem; van Asselen, Bram; van Soest, Theo; Kok, Jan; Raaymakers, Bas
Abstract: MRI guided radiotherapy devices are currently in clinical use. Detector responses are affected by the magnetic field and need to be characterized in terms of absorbed dose to water, D w, against primary standards under these conditions. The aim of this study was to commission a water calorimeter, accepted as the Dutch national standard for D w in MV photons and to validate its claimed standard uncertainty of 0.37% in the 7 MV photon beam of a pre-clinical MRI-linac in a 1.5 T magnetic field. To evaluate the primary standard on a fundamental basis, realisation of D w at 1.5 T was evaluated parameter by parameter. A thermodynamic description was given to demonstrate potential temperature effects due to the magneto-caloric effect (MCE). Methods were developed for measurement of depth, variation in detector distance and beam output in the bore of the MRI-linac. This resulted in D w measurements with a magnetic field of 1.5 T and, after ramp-down, without magnetic field. It was shown that the measurement of Δ T w and calorimeter corrections are either independent of or can be determined in a magnetic field. The chemical heat defect, h, was considered zero within its stated uncertainty, as for 0 T. Evaluation of the MCE and measurements done during magnet ramp-down, indicated no changes in the specific heat capacity of water. However, variations of the applied monitor system increased the uncertainty on beam output normalization. This study confirmed that the uncertainty for measurement of D w with a water calorimeter in a 1.5 T magnetic field is estimated to be the same as under conventional reference conditions. The VSL water calorimeter can be applied as a primary standard for D w in magnetic fields and is currently the only primary standard operable in a magnetic field that provides direct access to the international traceability framework.